2015
DOI: 10.2147/ndt.s61665
|View full text |Cite
|
Sign up to set email alerts
|

The clinical basis of orthorexia nervosa: emerging perspectives

Abstract: Orthorexia nervosa describes a pathological obsession with proper nutrition that is characterized by a restrictive diet, ritualized patterns of eating, and rigid avoidance of foods believed to be unhealthy or impure. Although prompted by a desire to achieve optimum health, orthorexia may lead to nutritional deficiencies, medical complications, and poor quality of life. Despite its being a distinct behavioral pattern that is frequently observed by clinicians, orthorexia has received very little empirical attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
380
0
42

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(436 citation statements)
references
References 59 publications
14
380
0
42
Order By: Relevance
“…The results represented in the present study with respect to the correct appetite are in tune with some studies in which the characteristics of people with orthorexia or with a pathological inclination are indicated for the food considered healthy; 23,27 that is, their ideology (what and how they think) is in line with the themes expressed in this paper "The World of Healthy Eating", "Why I Choose to Eat It" and "Absence of Infirmity as an Object of Ideal Consciousness". The set of strategies and constitutive mechanisms of experience (what do they do), are related with the theme "A recreated optimism", as an exercise of feedback of the condition between knowledge, manipulation and consumption of natural and organic food.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results represented in the present study with respect to the correct appetite are in tune with some studies in which the characteristics of people with orthorexia or with a pathological inclination are indicated for the food considered healthy; 23,27 that is, their ideology (what and how they think) is in line with the themes expressed in this paper "The World of Healthy Eating", "Why I Choose to Eat It" and "Absence of Infirmity as an Object of Ideal Consciousness". The set of strategies and constitutive mechanisms of experience (what do they do), are related with the theme "A recreated optimism", as an exercise of feedback of the condition between knowledge, manipulation and consumption of natural and organic food.…”
Section: Discussionsupporting
confidence: 86%
“…First developed by Bratman, the study has experienced modifications in its various validation attempts in other languages, as well as in its psychometric development to know psychosocial factors and comorbid psychopathology. 27 Consequently, due to insufficient research (ambiguity and variability in results) and because it is a multifaceted reality, a qualitative study approach is necessary in orthorexia; in fact, there are studies that rely on the requirement of an empirical-holistic approach and an interpretative analysis. 23 The increase in literature and other documents, relevant clinical experience and research studies in recent years circumscribe the relevance of the topic:…”
mentioning
confidence: 99%
“…Today, ON is not an accepted diagnostic category, that is, it is not included in the diagnostic manuals DSM-5 or ICD-10 (Varga, Dukay-Szabó, Túry, & Van Furth, 2013). Research has shown that ON shares many characteristics with diagnosed eating disorders (ED) and Obsessive Compulsive Disorder (Koven & Abry, 2015), and ED professionals suggest that ON deserves more attention in research and clinical practice (Vanderycken, 2011). In a Swedish context, ON is understood in terms of unhealthy exercise, and it has been linked to fitness gyms and emerging aggressive health and exercise trends (Håman, Barker-Ruchti, Patriksson, & Lindgren, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the psychosocial risks of imposing dietary change cannot be underplayed. These range from difficulties in socialisation and eating away from home through to the precipitation of eating disorders such as orthorexia nervosa 80. Third, the physiological effects of reducing FODMAP intake beyond those targeted to improve symptoms may have other implications.…”
Section: The Role Of Fodmaps In Ibsmentioning
confidence: 99%